2021
DOI: 10.1038/s41419-021-03659-y
|View full text |Cite
|
Sign up to set email alerts
|

Loss of FoxO3a prevents aortic aneurysm formation through maintenance of VSMC homeostasis

Abstract: Vascular smooth muscle cell (VSMC) phenotypic switching plays a critical role in the formation of abdominal aortic aneurysms (AAAs). FoxO3a is a key suppressor of VSMC homeostasis. We found that in human and animal AAA tissues, FoxO3a was upregulated, SM22α and α-smooth muscle actin (α-SMA) proteins were downregulated and synthetic phenotypic markers were upregulated, indicating that VSMC phenotypic switching occurred in these diseased tissues. In addition, in cultured VSMCs, significant enhancement of FoxO3a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…18,19 Contractile-to-synthetic phenotypic modulation of SMCs was earlier suggested to associate with both TAA and AAA. 20,21 Recent scRNA-seq and lineage-tracing studies have revealed a broad range of additional phenotypes for SMCs and ECs in vasculature (reviewed in Yap et al, 18 Ricard et al, 19 Grootaert et al, 22 Dejana et al 23 ) and suggested phenotypic switching and clonal expansion of specific cell subtypes in aortic aneurysms. 24,25…”
Section: Cell Phenotypes and Plasticitymentioning
confidence: 99%
“…18,19 Contractile-to-synthetic phenotypic modulation of SMCs was earlier suggested to associate with both TAA and AAA. 20,21 Recent scRNA-seq and lineage-tracing studies have revealed a broad range of additional phenotypes for SMCs and ECs in vasculature (reviewed in Yap et al, 18 Ricard et al, 19 Grootaert et al, 22 Dejana et al 23 ) and suggested phenotypic switching and clonal expansion of specific cell subtypes in aortic aneurysms. 24,25…”
Section: Cell Phenotypes and Plasticitymentioning
confidence: 99%
“…Moreover, five hub genes (FOXO3, DICER1, CCND2, IGF1R, and TNRC6B) were identified by the cytoHubba plugin based on the PPI network. Among them, FOXO3 was reported to promote VSMC phenotypic switching to accelerate aortic aneurysm formation ( Lu et al, 2021 ). DICER1 functioned as a ribonuclease and DICER-dependent miRNAs were important for VSMC development and functioned by regulating proliferation and contractile differentiation ( Albinsson et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through AT 1 R, AngII stimulation produces changes in the contractile machinery, constisting in decreased expression of contractiles markers such as αSMA (ACTA2), SM22a (TAGLN), and SMMHC (MYH11) (9,46). As others (41,47), in parallel with vascular remodeling, we observed significant changes in contractile markers expression in aortas under AngII infusion, with downregulation of "vascular smooth muscle contraction" pathway, and ACTA2 expression, but also TAGLN and MYH11 (see raw data). In addition, this phenotypic switch was maintained in time despite the end of AngII stimulation, for the "vascular smooth muscle contraction pathway", and also for αSMA expression, both at mRNA and protein levels (Figures 4B, 5A).…”
Section: Discussionmentioning
confidence: 99%